Implementation of Robotic Process Automation to a corporate Merger & acquisition process - Korpisalo, Matias Sauli Valtteri (My University, 2019)
This master’s thesis intends to find out how can a corporation implement a Robotic Process Automation (RPA) into their mergers & acquisitions (M&A) process. The research examines M&As and their motives and cross references this with RPA to identify possible improvements in the M&A process by using RPA. Mergers & acquisitions are an commonly used strategy when corporations raise they’re market cap and therefore have an strategy for inorganic growth. The success of M&As has been widely studied and multiple studies do show that they rarely create value for the corporation. RPA is a rather new technology for automating processes in the office environment, it has a lot of benefits and has been raising interest in corporations. By using RPA organizations can improve their knowledge-based work, however it is imperative to figure out the correct usage for RPA and what to automate in organizations. The theoretical framework for the study is based on research on M&As and on the research on RPA. RPA is still an upcoming technology, the current research focuses primarily what RPA is, rather than diving deeper in to the subject. The research was fulfilled in an international ICT-corporation, the material was gathered by using theme interviews and it was examined by using content analysis. The research identified that using RPA in mergers & acquisitions is rather challenging as the corporation in question is not a serial acquisitor. The amount of manual and routine labor in the processes are nominal. However, the possibilities for RPA in the corporation are the pre-screening phase and the Due Diligence processes. An interesting finding in the study was the need for creating tools for project management in mergers & acquisitions in the organization, as communication was seen as the essential problem to tackle.
Keywords: mergers & acquisitions; M&A; Robotic Process Automation; RPA; Process; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management